Inferring political and religious attitudes from composite faces perceived to be related to the dark triad personality traits. (November 2021) - Alper, Sinan; Bayrak, Fatih; Yilmaz, Onurcan
Abstract: We used composite face images perceived to have different levels of Dark Triad personality traits (narcissism, psychopathy, and Machiavellianism) and asked participants to predict these target individuals' religious and political identities. In Study 1 ( N = 550), Turkish participants rated faces with higher levels of perceived Dark Triad traits as less likely to be religious, to believe in God, and more likely to be left-winger, and to vote for a left-leaning party in all categories except for male narcissism. In a pre-registered follow-up study ( N = 1001), we recruited a nationally representative US sample and replicated the same results with minor differences regarding male and female narcissism, and voting preferences. Participants' own political and ideological identities and their stereotypical evaluation of the target groups were mostly ineffective in explaining their predictions. The results suggest that people can perceive faces with higher levels of Dark Triad traits as less religious and less conservative. Highlights: The first study was on a Turkish sample. We introduced faces associated with low and high levels of the Dark Triad (DT). High DT faces were perceived less likely to be religious and believe in God. They were perceived more likely to be left-winger and vote for a left-leaning party. We replicated most of these findings on a nationally representative US sample.